Sebuah Menata Diskusi Ruang Publik Online sebagai Sarana Penyebaran Konten Inspiratif Edukatif - Eni Kusti Rahayu; Joe Harrianto Setiawan; Muhammad Wanadli Rivan; Ni Putu Limarandani (Persatuan Wartawan Indonesia, 2023)
The Youtube channel Bincang Online Inspiratif (BIONS) Series presents educational content as an online public discussion space for enthusiasts. This study discusses the strategy of the BIONS Youtube account in disseminating these inspirational contents. The theory used is Peter Pringle's program strategy management to create and improve program quality and broadcast strategies to produce optimal impact. The research approach is qualitative with a case study method. The research findings are that online talk shows are planned through creative strategies starting from pre-production, production, and post-production to achieve broadcast success. The pre-production stage is an area to determine the theme, sources, and shooting layout before stepping into the production stage using zoom and YouTube live streaming. The next step is post-production, which is the core of dissemination, including editing, evaluation and marketing publications. To get viewers and account subscribers, it is done by distributing flyers on Instagram, WA groups, and various other supporting communication facilities, as well as making luckydraw as an effort to attract new viewers and maintain audience loyalty.